PREFERENSI PETANI TERHADAP PRODUK OLAHAN KELAPA DI DESA KANCINAA KECAMATAN PASARWAJO KABUPATEN BUTON - Misy Rahmawati La Guu; Musadar Mappasomba; Mardin Mardin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The objective of this study is twofold: firstly, to ascertain the preferences of coconut farmers with regard to processed coconut products; and secondly, to investigate the coconut processing process in Kancinaa Village. The population under investigation in this study consisted of all coconut farmers in Kancinaa Village. The informants were selected using the purposive method, with several considerations taken into account, including the number of informants in the study, which was nine coconut farmers. This research employs a qualitative data collection methodology. In order to collect the necessary data, the researchers employed a combination of observation and semi-structured interviews, with the use of interview guides to facilitate the process. The present study focuses on the preferences of farmers with regard to processed coconut products. The research data were analyzed qualitatively using the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the predominant preference among coconut farmers in Kancinaa Village for processed coconut products is wet processing, which results in the production of cooking oil. Furthermore, dry processing and selling by the log are alternative options for coconut farmers when selecting a business model. The preference of farmers in Kancinaa Village in choosing coconut processing is influenced by a number of factors, including social, psychological, and economic considerations. Among these three factors, economic factors are the most significant, including production costs, selling prices, and market demand. Coconut processing in Kancinaa Village can be classified into three main categories: wet processing, which results in cooking oil products; dry processing, which results in fried coconut products; and selling coconuts in the form of logs or without processing.